Impact of Chemotherapy upon Lifestyle for the Patient with BIadder Cancer - Khalida M. Khuder, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: The study aimed to determine the effect of chemotherapy on the life style of patients whoreceive chemotherapy.Methodology: A descriptive study was conducted in Specialty Surgery Teaching Hospital, Al-yamokTeaching Hospital, and Radiation and Nuclear Medicine Hospital in Baghdad for the period from May2007 to October 2008. A purposive "non-probability" sample of (loo) patients with bladder cancerwho receive chemotherapy where concerned in this study.A questionnaire fom was constnicted for the purpose of the study and it was comprised oftwo parts. The questiormaire consists of (125) items. They include (1) demographic information (2)assessment of lifestyle dimension. The content validity of the questionnaire was determined through apanel of (13) experts. Data were collected by the investigator who interviewed those patients and filledout the constructed questionnaire form.The data were analyzed by using descriptive statistical approach (frequency, percentage andmean of scores) and inferential statistical approach (chi-square, standard deviation and correlationcoefficient).Results: The findings of the study have revealed that most of patients with bladder cancer who receivechemotherapy were of 60.3) years mean age, mostly males, living in urban area, married and hadchildren, primary school graduate, retired with barely sufficient monthly income taking chemotherapyby Foley's catheter and duration of disease 1-5 years.Recommendations: The study recommended that an education program to be developed andimplemented of patients with bladder cancer who were under chemotherapy treatment.